Novel biallelic COL25A1 variants broaden the clinical spectrum from congenital cranial dysinnervation disorders to fetal lethal phenotypes - Harms, Frederike Leonie; Müller, Christian; Kortüm, Fanny; Hempel, Maja; Alawi, Malik; Zaki, Maha S.; Elhossini, Rasha M.; Abdel-Hamid, Mohamed S.; AlAbdi, Lama; Alkuraya, Fowzan S.; Kurdi, Wesam; Celse, Tristan; et al. (European journal of human genetics, 2025)
Biallelic variants in COL25A1 have been associated with isolated congenital cranial dysinnervation disorders (CCDDs) and arthrogryposis multiplex congenital (AMC) with or without CCDD. COL25A1 encodes collagen XXV that belongs to the subfamily of membrane-associated collagens with interrupted triple helices. COL25A1 contains four non-collagenous and three collagenous domains. Three alternatively spliced COL25A1 transcript variants are known. In mice, Col25a1 is required for intramuscular motor innervation and cranial motor neuron development. We report seven subjects with novel biallelic COL25A1 pathogenic variants, including three AMC-affected individuals, one of whom died in infancy, and four unrelated fetuses. We expand the associated phenotypic spectrum as fetuses showed lethal phenotypes including reduced or no movement, contractures, and hydrops in three and growth retardation and skeletal abnormalities in one. The molecular spectrum includes two microdeletions encompassing several 5′ or 3′ exons, two missense, one nonsense, one frameshift, and one variant affecting splicing. In fibroblasts of the subject who was compound heterozygous for the c.367G > C and c.1198G > T variants, we identified skipping of exon 3 in COL25A1 mRNAs due to the G-to-C change. These aberrantly spliced transcripts were subject to nonsense-mediated mRNA decay. Analysis of transcriptome sequencing data from primary human fibroblasts without COL25A1 pathogenic variants revealed novel COL25A1 exon-exon junctions and 13 not previously annotated alternatively spliced in-frame exons. We hypothesized that interindividual variation in the splicing of COL25A1 exons in different tissues may underlie the variable phenotypes in the affected individuals.